Conservation biology voices from the tropics - Sodhi, Navjot S.; Gibson, Luke; Raven, Peter H. (Chichester, West Sussex, [England] Wiley Blackwell, 2013)
The late Navjot Sodhi conceived the idea of this book as a way of bringing the views of biologists living and working in the tropics to the forefront of our conservation planning for these biologically rich habitats facing increasing pressures from expanding human populations. In its 30 chapters, 55 authors present their views on the conservation problems they face and the solutions they have adopted in response. Human populations in tropical countries are projected to grow by more than 2.5 billion people over the next few decades, with expectations of increased consumption levels growing even more rapidly than the numbers of people. Clearly there will be a need for more trained conservationists and biologists to learn from the voices in this volume and further improve conservation efforts in the tropics. Significant levels of local involvement are essential to conservation success, with the rights of local people fully recognized, protected and fostered by governmental and international assistance. Overarching conservation plans are necessary, but cannot in themselves lead to success. Instead, effective long term conservation in the tropics requires the full participation of local people, organizations and governments. We hope that the individual experiences presented in the pages of this book will provide useful models that may serve to build better and more sustainable lives for the people who live in the tropics and lead to the continued survival of as many species and functioning ecosystems as possible--Book jacket.
Includes bibliographical references and index.
Keywords: Nature conservation -- Tropics; Conservation biology -- Tropics